Incidence and Predictors of Reperfusion Arrhythmia on STEMI Patients and Its Association with Infarct and Reperfusion Therapy Factors: A Cross-Sectional Study - Fairuz Kamila, Rizqi Apsari; Budi Baktijasa Dharmajati; Mahrus A. Rahman; Bambang Herwanto (Archives of The Medicine and Case Reports, 2024)
Reperfusion arrhythmia was one of the markers of reperfusion in acute myocardial infarction (AMI). However, as the study developed, there were controversial findings of the meaning of reperfusion arrhythmias as a marker of successful reperfusion or persistent ischemia. The study aims to analyze the occurrence of arrhythmia in patients with STEMI undergoing reperfusion therapy with primary PCI or thrombolytic at Dr. Soetomo General Hospital Surabaya. This study is a retrospective observational study with a cross-sectional design using medical records as a data source. The occurrence of arrhythmias in patients was observed within 24 hours after the reperfusion therapy procedure. A total of 82 STEMI patients undergoing reperfusion therapy were observed (78 primary PCI and 4 thrombolytic). The total rate of reperfusion arrhythmia beyond the first 24 hours after the procedure was 54.9% (n = 45). There was no significant association for the baseline clinical characteristics of patients with the risk of reperfusion arrhythmia except for the heart rate on admission (p-value=0.003). The choice of reperfusion therapy (thrombolytic or PPCI) and time to revascularization were also not significantly associated with the occurrence of arrhythmias. Infarct characteristics, including the location and the number of blood vessels diseased, also did not have a significant relationship with the incidence of arrhythmias. Reperfusion therapy remains, resulting in a higher incidence of reperfusion arrhythmias. The incidence of reperfusion arrhythmias may be influenced by various factors. Thus, close monitoring beyond the first 24 hours after reperfusion therapy is required.